Sport on the Move: The Unfolding Impact of Mobile Communications on the Media Sport Content Economy. (December 2014) - Hutchins, Brett
The increased popularity of mobile smartphones and tablet computers in developed economies is transforming how and where sports footage, highlights and information are accessed. These developments are contributing to new commercial arrangements in the media sport sector, as well as legal conflicts over sought-after content that is transferable and reproduced across broadcast (pay-for-view and free-to-air television), online (desktop and laptop computers), and mobile platforms (smartphone and tablets). In particular, mobile and wireless communications highlight that the media sport content economy is now "on the move" from technology, commercial, regulatory, and legal perspectives. This article outlines factors that are determining how this economy functions in relation to mobile media, with an emphasis on the complex and sometimes unpredictable relationship between content production, distribution, platforms, and access.